Carbon and nitrogen stocks in the High Biodiversity Silvopastoral System: applied nucleation enabling low carbon livestock production (Research, Society and Development, 2020)
Agriculture has proved to be one of the main sources of greenhouse gases (GHG). Large part of this GHG is related to the production system or inadequate management. This study analyzed the effects of the High Biodiversity Silvopastoral System (SPSnuclei) on pasture cover, and carbon and nitrogen stocks when implanted on treeless pastures (PSA). The variables were measured in three situations, two areas within the SPSnuclei - area close to the nuclei (APN) and a sunny area between the  (p